Transforming trade law in the digital era: Navigating challenges and seizing opportunities for legal reforms in Indonesia's evolving trade landscape - Abdurrahim (Ex Aequo Et Bono Journal Of Law, 2025)
Background : In Indonesia, the transformation of trade law in the IT and Internet era presents significant challenges and opportunities. Businesses have changed, markets have expanded, and digitalization has created new economic opportunities. However, these changes have also raised a number of legal questions, including consumer protection, data security, the legality of electronic transactions, and the role of government in regulating digital commerce. This article analyzes how Indonesian laws and regulations have adapted to these changes and examines the challenges of implementing regulations in the face of rapid technological developments. This article provides a comprehensive overview of the direction of trade law in the digital era and its impact on the Indonesian economy and society, with a focus on the policies implemented and opportunities for future regulatory improvement. Methods: This study focuses on the challenges and opportunities arising from technological advances and e-commerce, and discusses changes in trade law in the digital era in Indonesia. A normative legal approach is used in this study. Digital trade law is examined using a normative approach. Findings: This study highlights several issues, including regulations that do not reflect technological advances, inadequate consumer protection, cybersecurity risks, and regulations that mix digital and traditional business practices. In contrast, the rapid growth of e-commerce in Indonesia, government efforts to build a digital ecosystem, and the potential for global cooperation to resolve international issues present significant opportunities. Conclusions: The results of this study highlight the need for more flexible and comprehensive legal reforms to deal with developments in the digital era. Harmonization of cross-sector regulations, increased cybersecurity, and strengthened consumer protection are key to seizing the opportunities arising from the growth of digital trade in Indonesia. Novelty/Originality of this Study: The study found that digital trade regulations in Indonesia are still lagging behind technological developments, especially in consumer protection and cybersecurity. However, opportunities arise from the government's efforts to build a digital ecosystem and the potential for global cooperation to improve digital trade regulations.